1999
DOI: 10.1038/19328
|View full text |Cite
|
Sign up to set email alerts
|

Direct control of the Forkhead transcription factor AFX by protein kinase B

Abstract: The phosphatidylinositol-3-OH-kinase (PI(3)K) effector protein kinase B regulates certain insulin-responsive genes, but the transcription factors regulated by protein kinase B have yet to be identified. Genetic analysis in Caenorhabditis elegans has shown that the Forkhead transcription factor daf-16 is regulated by a pathway consisting of insulin-receptor-like daf-2 and PI(3)K-like age-1. Here we show that protein kinase B phosphorylates AFX, a human orthologue of daf-16, both in vitro and in vivo. Inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
803
3
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,001 publications
(841 citation statements)
references
References 28 publications
20
803
3
5
Order By: Relevance
“…After PtdIns-3,4,5-P3 binding, Akt translocates to the plasma membrane where key serine/threonine residues are phosphorylated by PDKs (Downward, 1998b). Transfection studies have shown that Akt, after being activated by IGF-I/insulin in this manner, can phosphorylate members of the forkhead family transcription factors (Brunet et al, 1999;Guo et al, 1999;Kops et al, 1999;Nakae et al, 1999;Rena et al, 1999;Tang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After PtdIns-3,4,5-P3 binding, Akt translocates to the plasma membrane where key serine/threonine residues are phosphorylated by PDKs (Downward, 1998b). Transfection studies have shown that Akt, after being activated by IGF-I/insulin in this manner, can phosphorylate members of the forkhead family transcription factors (Brunet et al, 1999;Guo et al, 1999;Kops et al, 1999;Nakae et al, 1999;Rena et al, 1999;Tang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The activated Akt can then phosphorylate substrates such as BAD (Datta et al, 1997) and Caspase 9 (Cardone et al, 1998). Activated Akt also translocates to the nucleus Meier et al, 1997) where, as recently discovered, it can phosphorylate the forkhead family transcription factors (Brunet et al, 1999;Guo et al, 1999;Kops et al, 1999;Nakae et al, 1999;Rena et al, 1999;Tang et al, 1999).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…FOXOs are extensively regulated by post-translational modifications, including phosphorylation, acetylation and ubiquitination (Obsil and Obsilova, 2008). For example, insulin induces the phosphorylation of FOXO1, FOXO3 and FOXO4 through Akt/protein kinase B, leading to the exclusion of FOXO from the nucleus and the inhibition of FOXO transcription activities (Biggs et al, 1999;Brunet et al, 1999;Kops et al, 1999;Rena et al, 1999;Takaishi et al, 1999). On the other hand, in response to stress, MST1 (Lehtinen et al, 2006) and JNK1 (Essers et al, 2004) phosphorylate FOXO factors at different sites, resulting in nuclear translocation and transactivation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Activated Akt phosphorylates and inhibits several proapoptotic proteins, such as Bad, caspase-9 and the Forkhead transcription factors that include FKHRL1, FKHR and AFX, leading to cell survival. [11][12][13][14][15] Although several growth factors (such as IGF-I, TGF, EPO, PDGF) [16][17][18][19] have been found to induce FKHRL1 phosphorylation via the Akt pathway, the role of Akt in BDNF regulation of FKHRL1 has not been explored. Forkhead transcription factor-induced cell death appears to be mediated by transcriptional regulation of a number of genes including Fas ligand (Fasl) 15,20 and Bim, a BH3 only domain protein that modulates the intrinsic mitochondrial death pathway.…”
mentioning
confidence: 99%